Analyses of decalcification process of calcium silicate hydrate (C-S-H) phase. Issue 1 (April 2019) - Sun, Can; Liu, Lin; Du, Yuanbo
Abstract: To comprehensively learn the dynamic decalcification process of C-S-H, changes of calcium-to-silicon molar ratio (Ca/Si ratio) of C-S-H powders with NH4 NO3 solution concentration and with decalcification time as well as decalcification homogeneity are investigated. C-S-H particles are decalcified by NH4 NO3 solution of different concentration at different time. Ca/Si ratios on the outer surface and inside the C-S-H particles were measured by Scanning Electron Microscope (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX). X-ray diffraction (XRD) tests were conducted to study the crystalline structure of C-S-H. It is found that the calcium at the edge of C-S-H particles is preferentially removed, and the decalcification gradually progress inside as the leaching period is extended. Instead of immersing C-S-H powders in the standard 6 mol/L NH4 NO3 solution for a predetermined time, it is recommended that C-S-H powders are immersed in NH4 NO3 solution of different concentration for extended time periods to obtain homogeneously decalcified C-S-H particles.